ALLOCATION OF BIDIKMISI SCHOLARSHIPS AND LEARNING INDEPENDENCE TOWARDS LEARNING ACHIEVEMENT OF BIDIKMISI STUDENTS IN JAKARTA STATE UNIVERSITY 2018 - Fitrianingsih; Mardi; Ahmad Fauzi (Transpublika Publisher, 2022)
This study aims to determine the effect of Bidikmisi scholarship and learning independence on student achievement. The method used is the quantitative method. The population in this study were students who received in the 2018 State University Bidikmisi scholarship. The sampling technique used the proportional random technique as many as 233 people. Data collection using documentation and questionnaire methods. The data analysis technique used descriptive statistics, multiple linear regression test, normality test, linearity test, t test, F test, and the coefficient of determination processed with SPSS version 25. Tests from the analysis showed that the allocator of the Bidikmisi scholarship and learning independence partially and simultaneously had a positive and significant effect on student academic achievement.